Edukasi tentang Stop Bullying Pada Siswa-siswi Madrasah Ibtidaiyah Tahfidz HDWR Bantul - Evi Ni’matuzzakiyah (jurnal ABDIMAS Indonesia, 2025)
Bullying is a social and psychological issue that frequently occurs in elementary school settings, including madrasah ibtidaiyah. This behavior negatively affects students’ emotional, social, and academic development. This community service program aimed to provide anti-bullying education to elementary school students through interactive and Islamic value-based approaches. Activities included educational sessions, group discussions, role-playing, moral reflections, and class agreements against bullying. The program revealed students’ enthusiasm in identifying bullying behavior and understanding the importance of mutual respect. It also encouraged collective commitment through a child-friendly classroom declaration. This initiative is expected to contribute to building a safe, inclusive, and supportive school environment for holistic student development.